2019
DOI: 10.1002/mrc.4872
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new cyano‐substituted analogues of Tröger's bases from bromo‐derivatives. A stereochemical dependence of long‐range (nJHH, n = 4, 5, and 6) proton–proton and proton–carbon (nJCH, n = 1, 2, 3, 4, and 5) coupling constants of these compounds

Abstract: A free‐catalyst microwave‐assisted cyanation of brominated Tröger's base derivatives (2a‐f) is reported. The procedure is simple, efficient, and clean affording the nitrile compounds (3a‐e, I) in very good yields. Complete assignment of 1H and 13C chemical shifts of 2a‐f, I and 3a‐d, I was achieved using gradient selected 1D nuclear magnetic resonance (NMR) techniques (1D zTOCSY, PSYCHE, DPFGSE NOE, and DEPT), homonuclear 2D NMR techniques (gCOSY and zTOCSY), and heteronuclear 2D NMR techniques (gHSQCAD/or pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Theoretical and practical implications of this type of competitive reactions have been extensively discussed in relation to the combination of free radicals in homogeneous and heterogeneous media, see for example Chesta et al Hence, a‐TB reaction yields reported in Scheme (products 6z , 8z and 9z ) must be analyzed within the framework of the concepts discussed above. Symmetrical TB 5z was obtained in ~96 % yield, which agrees well with previous reports . Compound 6z was obtained by ca.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Theoretical and practical implications of this type of competitive reactions have been extensively discussed in relation to the combination of free radicals in homogeneous and heterogeneous media, see for example Chesta et al Hence, a‐TB reaction yields reported in Scheme (products 6z , 8z and 9z ) must be analyzed within the framework of the concepts discussed above. Symmetrical TB 5z was obtained in ~96 % yield, which agrees well with previous reports . Compound 6z was obtained by ca.…”
Section: Resultssupporting
confidence: 91%
“…Tröger′s bases (TB) were prepared from anilines in trifluoroacetic acid (TFA) and characterized as described before . The yields for the five model syntheses are summarized in Scheme .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations